The dissemination of ST80-SCCmec-IV community-associated methicillin resistant Staphylococcus aureus clone in Kuwait hospitals - Sarkhoo Eiman; Udo Edet E (BMC, 2010)
Abstract Background Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is a global healthcare problem. The purpose of this study was to characterize CA-MRSA clones and their distribution in Kuwait hospitals. Methods In total, 135 CA-MRSA isolates, carrying the SCCmec IV or V genetic elements, isolated in eight hospitals were characterized using antibiogram, pulsed-field gel electrophoresis, multilocus sequence typing, and carriage of genes for Panton-Valentine Leukocidin (PVL), capsular polysaccharides types (cap) 5 and 8, accessory genes regulators (agr), Staphylococcal enterotoxins (SE) and toxic shock syndrome toxin 1 (tst). Results They were susceptible to vancomycin, teicoplanin and linezolid but resistant to kanamycin (62%), fusidic acid (42.2%), tetracycline (39.3%), erythromycin and clindamycin (21.5%), gentamicin (5.9%), streptomycin (6.7%), trimethoprim (5.9%), mupirocin (6.6%) and cadmium acetate (82.2%). They consisted of 10 pulsotypes with the majority belonging to PFGE type I (51.1%), type II (22.2%), type IV (13.3%) and type III (3.7%). They belonged to 10 sequence types (ST) comprising ST80 (51.1%), ST30 (22.2%), ST5 (14.1%), ST1 (4.45), ST6 (3.7%), ST88 (1.5%), ST834 (1.5%), ST8 (0.7%), ST46 (0.7%) and ST950 (0.7%). Genes for PVL, cap 8, cap 5 and agr III, agr I and agr II were detected in 61.5%, 77.3%, 20.7% and 62.2%, 17% and 8.1% of the isolates respectively. Nine (6.7%) isolates contained tst while 103 isolates were positive for SE genes with sei (63.0%), seg (41.5%) and sed (29.6%) as the common SE genes. Conclusions ST80-SCCmecIV was the most common CA-MRSA clone in Kuwait hospitals presenting new challenges for infection control.